Pre-Labour Rupture of Membranes: A Case Report, Management & Literature Review - Kimera, Charles Lukanga; Lukolo, Linda Ndeshipandula (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2019)
Rupture of membranes during pregnancy before labour begins, referred to as premature rupture of membranes (PROM), is a known risk factor for subsequent maternal and foetal/neonatal infection although pre-existing infection may at times be the cause of membrane rupture. This infection may lead to poor pregnancy outcome if appropriate management is not instituted in time. Recognition of the period of rupture, by proper history taking, is of paramount importance as further management of the mother will depend on this. This paper reviews a case report of a mismanaged pre-labour rupture of membranes which resulted in loss of a foetus/baby in one of the public hospitals.